Barriers to the Implementation of Continuous Positive Airway Pressure (Cpap) Ventilation in Neonates at Birthplace in Tertiary Care Teaching Hospitals - Hussain, Shabbir; Hussain, Moeez; Ullah, Inayat; Shah, Syed Awais Ul Hassan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To explore different barriers to the implementation of continuous positive airway pressure ventilation in neonates at the birthplace. Study Design: Mixed method study. Place and Duration of Study: Combined Military Hospital and Pak-Emirates Military Hospital Rawalpindi Pakistan, from Jan to Jun 2021. Methodology: Health care professionals involved in neonatal care at these two hospitals were included. The sample size was predetermined (60 in total). Participants’ written response was obtained on an open-ended self-administered questionnaire distributed in person. All enrolled participants responded. Thematic analysis of data was carried out. Results: The participants were predominantly female (66.66%), aged 20-30 (66.66%). Eight (13.33%) had received CPAP training. The majority (83.33%) think that CPAP is useful, but only 10 (33.33%) have CPAP experience at the delivery suite. The first theme category was "Health professional related". Participants reported lack of awareness, motivation and training, understaffing, communication gap, responsibility conflict and rapid turnover of health professionals as a barricade. The second theme category was "organization/system related". Nonexistence of CPAP written guidelines, Obstetrics/ Gynaecology health professionals’ unawareness about CPAP, CPAP implementation inferiority/ subservience/ subordination and multi-discipline hierarchy were deterrents. The third emerged theme category was "logistics/resources". Shortage, failed continuous equipment supply, and poor infrastructure is major hurdles. Conclusion: This study has identified weak areas/glitches on which efforts should be focused and suggested recommenddations to overcome hurdles and implement CPAP use at birthplaces.